Planejamento ótimo de plantio e colheita da cana-de-açúcar utilizando graus-dias - Isler, Paulo Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil is the world's largest sugarcane producer and sugar exporter, what directly influences the Brazilian economy. There is a constant introduction of new kinds of sugarcane in the market, more productive, pest resistant and with a good development in several kinds of climate and lands; new planting and harvesting methodologies arise as well as more efficient machines. However, with the extended cultivated area and this great number of varieties, a necessity of new technologies appears in order to help deciding the proper variety to be planted, based on the climate and land, as well as in the right period of sugarcane planting and harvesting, what can be reached with a well done planning. A crop planning with this profile allows the profitability to increase and make the process more effective, in other words, it gets higher productivity of sugarcane in a same cultivated area. But this planning process becomes even more complex whenever the constant climate changes are considered. The climate is one of the main factors that influence the biomass quality of the sugarcane which is used in this sector. This way, this work comes up with a methodology for the optimized planting and harvest planning of sugarcane, considering the climate changes. For this purpose, the degree days method is used, which is based in the ideal temperature range for the development of the plant. There is a mathematic model proposed to help choosing the variety to be planted, as well as the period of sugarcane planting and harvest, considering that the sugarcane should be harvested in the right maturation period calculated from the number of degree days accumulated, exploring then its energetic potential and meeting the factory's demand. The proposed methodology was applied in two producing regions which present great climate differences. The proposed methodology was robust, since even applied in different climatic regions it ...

O Brasil é o maior produtor mundial de cana-de-açúcar e o maior exportador mundial de açúcar, o que vem influenciar diretamente a economia brasileira. Constantemente são introduzidas no mercado novas variedades de cana, mais produtivas, resistentes a pragas e com bom desenvolvimento em diversos tipos de clima e solos; surgem novas metodologias de plantio e colheita e máquinas mais eficientes. Devido a extensa área plantada e ao grande número de variedades, surge a necessidade de novas tecnologias para auxílio nas tomadas de decisões da correta variedade a ser plantada, baseado no clima e solo, assim como no correto período de plantio e colheita da cana, o que pode ser alcançado com um bom planejamento. Um planejamento da cultura com este perfil permite aumentar a rentabilidade e tornar o processo mais eficiente, ou seja, conseguir maiores produtividades da cana numa mesma área plantada. Mas esse processo de planejamento torna-se ainda mais complexo quando é levado em consideração as constantes alterações climáticas. O clima é um dos principais fatores que influencia na qualidade da biomassa da cana-de-açúcar utilizada no setor sucroalcooleiro. Neste sentido, este trabalho propõe uma metodologia para o planejamento otimizado de plantio e colheita da cana-de-açúcar, considerando as mudanças climáticas. Para isto, é utilizado o método de Graus-dias, que baseia-se na faixa de temperatura ideal para o desenvolvimento da planta. Propõe-se um modelo ...
Optimal planning of planting and harvesting of sugarcane using degree days
Keywords: Plantas - Efeito da temperatura; Cana-de-açúcar - Plantio; Cana-de-açúcar - Colheita; Algoritmos genéticos; Sugar cane